DARI KERAJINAN AMAI SETIA KE SOENTING MELAYOE STRATEGI ROHANA KUDDUS DALAM MELAWAN KETERTINDASAN PEREMPUAN DI MINANGKABAU - Susi Ratna Sari (Universitas Islam Negeri Imam Bonjol Padang, 2016)
Accross the periods of time, women did not pass the live without any obstacles, both the social and the cultural constructions they become isolated, weaken and do not get simmilar turns as well man can have for realizing their existance. This kind of condition laid some women social movements or organizations that aimed at fighting for their freedom and right. On of the movement is Rohana Kuddus (Rohana Kuddus, one of its efforts is building the school fo female student. Another effort if creating the newspaper which was concerned with woman issues as the condition do not give woman the ballaced changes to take a parts in all live aspects. As this movement built the function tent be improved, becoming an enterprenuer office. As the result nowdays it become a well known one. This movement facilitate both educational and economical supports that make them find them self independent while the movement through newspapers Rohana Kuddus has established BC, where the newspaper was the only female newspaper became the first in Indonesia that serves as an educator, controler and critics to the society in related with woman malltreatment. Rohana Kuddus movement made of this; it can contribute in the welfare of women so that woman will be avoided from the violence.